The Role of Performance Measurement Systems and Innovative Culture in Promoting Innovative Work Behavior: The Mediating Effect of Organizational Support - Ardiansyah, Septian Rino; Hadi, Syamsul; Lukitaningsih, Ambar (JURNAL MANAJEMEN MOTIVASI, 2025)
This study explores how performance measurement systems and innovative culture influence innovative work behavior, with perceived organizational support as a mediator. Conducted at the Giwangan Terminal Office in Yogyakarta with 105 employees, data were collected via questionnaires and analyzed using SmartPLS 4. Results show that performance measurement systems impact innovative behavior only indirectly through organizational support, while innovative culture affects it both directly and indirectly. The findings highlight the importance of fair performance systems and a supportive, innovation-driven culture in fostering employee creativity and strengthening organizational competitiveness.